The Future of the SDR in Light of Changes in the International Monetary System. (International Monetary Fund, 1996)
This book edited by Michael Mussa, James M. Boughton, and Peter Isard, records the proceedings of a seminar held at the IMF in March 1996 on the future of the special drawing right (SDR), given changes in the international monetary system since the inception of the SDR. The seminar focuses on the differences in opinion in the international community on the desirability or feasibility of an additional allocation of SDRs.